2020
DOI: 10.1128/mbio.02903-19
|View full text |Cite
|
Sign up to set email alerts
|

CpG Frequency in the 5′ Third of the env Gene Determines Sensitivity of Primary HIV-1 Strains to the Zinc-Finger Antiviral Protein

Abstract: CpG dinucleotide suppression has been reported to allow HIV-1 to evade inhibition by the zinc-finger antiviral protein (ZAP). Here, we show that primate lentiviruses display marked differences in CpG frequencies across their genome, ranging from 0.44% in simian immunodeficiency virus SIVwrc from Western red colobus to 2.3% in SIVmon infecting mona monkeys. Moreover, functional analyses of a large panel of human and simian immunodeficiency viruses revealed that the magnitude of CpG suppression does not correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 49 publications
2
57
0
Order By: Relevance
“…On average, the CpG frequency in the HIV-1 genome is substantially lower than in the SARS-CoV-2 genome. However, recently reported data show that a region of CpGs at the beginning of the env gene of HIV-1 rather than overall genomic content determines the susceptibility of HIV-1 to inhibition by ZAP (47). Thus, it is conceivable that parts of the SARS-CoV-2 genome may still be ZAP sensitive, although it shows strong CpG suppression throughout most parts of its genome.…”
Section: Discussionmentioning
confidence: 99%
“…On average, the CpG frequency in the HIV-1 genome is substantially lower than in the SARS-CoV-2 genome. However, recently reported data show that a region of CpGs at the beginning of the env gene of HIV-1 rather than overall genomic content determines the susceptibility of HIV-1 to inhibition by ZAP (47). Thus, it is conceivable that parts of the SARS-CoV-2 genome may still be ZAP sensitive, although it shows strong CpG suppression throughout most parts of its genome.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported that age-associated microbial dysbiosis aggravates intestinal permeability and systemic inflammation (7). Furthermore, results from our previous studies in mice showed that CR changed gut microbiota into a Lactobacillus-dominated structure, and a strain of Lactobacillus murinus isolated from CR mice contributed to the alleviation of aging-associated inflammation, thereby demonstrating a microbiota-dependent mechanism for the metabolic improvement by CR (810).…”
Section: Introductionmentioning
confidence: 96%
“…In the case of HIV-1 RNA, ZAP binds to a region with high CpG density [ 21 ]. Further studies indicate that the location rather than the total number of CpG dinucleotides is important [ 22 ]. ZAP lacks intrinsic RNase activity but recruits the 5’ and 3’ RNA degradation machinery [ 15 , 23 25 ].…”
Section: Introductionmentioning
confidence: 99%